Enhancing Business English Skills: Addressing Speaking Challenges in the Management Department - Winantaka, Binar (Universitas Negeri Yogyakarta, 2024)
This investigation assesses the inadequacy of current business English materials for economic students at Indonesian colleges, with a focus on integration issues impacting speaking proficiency. Conducted with 80 management students in Yogyakarta, the study utilized 38 questionnaires to analyze students' needs, deficiencies, and preferences in business English. Data were processed using Likert scales and interval categorization to highlight key areas of concern. Results indicate a critical need for enhanced instruction across the four linguistic skills to address speaking difficulties. Students reported significant challenges in acquiring business English and developing speaking skills, expressing a preference for a more dynamic learning model. The findings emphasize the necessity for curriculum reforms and the development of specialized resources to improve business English proficiency.